Расчёт влияния обледенения на эффективность отбора низкопотенциальной теплоты от водной среды - Харченко, В. В.; Сычёв, А. О. (Енергетика і автоматика, 2017)
CALCULATION OF INFLUENCE OF ICING ON EFFECTIVENESS OF LOW-POTENTIAL HEAT SELECTION FROM WATER ENVIRONMENT V. Kharchenko, A. Sychev In recent years, the widespread use of, primarily, abroad, began to receive heat pump systems for heating and hot water supply. Particularly promising is the use of such systems in rural areas in the absence of district heating networks to provide households with thermal energy, whose share in the energy balance of agricultural production usually exceeds 60%. Heat pump systems using the heat of the watercourses are not inferior in performance to installations with ground heat exchangers at substantially lower capital costs. However, the methods used so far to select low-grade heat from the aquatic environment, usually based on the use of a large volume of polyethylene pipes immersed in water, have a number of shortcomings and do not allow to take full advantage of the advantages of such a source of heat. When selecting a heat pump for low-grade heat from a watercourse by means of immersion heat exchangers, it is possible that the temperature on the outside of the heat exchange surface is below the freezing point of water. This will lead to the formation of an ice crust on the surface, which changes the heat exchange regime. The aim of the study was to study the effect of icing on the efficiency of selection of low-grade heat from the aquatic environment. To study the processes taking place in systems of selection of low-potential heat from a watercourse under the conditions of ice confinement to the heat exchange surface, a mathematical model was developed. In order to assess the effect of icing on the heat transfer intensity and the characteristics of a submerged heat exchanger, it was decided to use the coolant temperature as one of the main parameters characterizing the heat exchange process, primarily the temperature of the coolant at the inlet to the heat exchanger and the temperature at the outlet from it. In order to select the required heat flux from a given heat exchanger with known parameters, a certain temperature gradient must be provided between the heat carrier in the heat exchanger tube and the water in the watercourse, which is reached at a certain value of the coolant inlet temperature in the heat exchanger It is established that a significant deterioration in the heat exchange characteristics begins only when the average level of the linear heat flux density is reached, corresponding to the almost complete icing of the heat exchange tube. Partial icing of the heat exchange tube does not lead to a significant deterioration of the heat exchange characteristics. To identify the cause of this phenomenon, graphs were constructed that describe the variation in the parameters along the length of the partially iced heat exchange tube for a particular case. This ratio of the initial parameters (selected heat flow, coolant flow, water temperature in the watercourse, flow velocity) was taken, which leads to the formation of a steady layer of ice approximately half the length of the coil, the total length of the pipes is 45 meters. In this case, a thick layer of ice in the initial section of the heat exchange tube significantly worsens the heat transfer, already at the end of the ice-covered area, the density of the heat flux begins to exceed the corresponding value for the case of the absence of an ice layer, which is associated with a lower coolant temperature and, accordingly, a higher temperature gradient. As a result, at the outlet of the heat exchanger, the value of the coolant temperature and the value of the total heat flux selected are only slightly below the corresponding values for the case of absence of icing. Conclusions. The results of the study showed that the partial icing of the heat exchange surface does not have a critical value on the heat exchange parameters and can be an acceptable phenomenon in the operation of heat pump installations using low potential heat of surface waters. Due to the partial removal of restrictions on the maximum heat flux density from water to the heat carrier and, correspondingly, to the minimum surface area of the water-heat exchanger heat exchanger associated with preventing icing of the heat exchanger surface, it becomes possible to use more compact heat exchangers with a small working surface and high heat flux density, which can be important in the limited space available to accommodate the heat exchanger for the watercourse. In addition, in addition to reducing the mass-dimension parameters of the heat exchanger, it becomes possible to reduce the volume of the heat carrier and reduce the hydraulic losses during its circulation.